2020
DOI: 10.24093/awej/vol11no1.8
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles of Indonesian EFL Students: Culture and Learning

Abstract: Learners' success in language learning is affected by many factors, including age, aptitude, and intelligence, cognitive style, attitudes, motivation, and personality. Besides, learning strategies and learning styles also help to succeed in language learning. This paper discusses the learning style preferences of the first-year students at English Department Universitas Brawijaya Malang, Indonesia. There were two problems that attempted to be answered; first, what are the learning styles used by the students, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 3 publications
3
12
1
Order By: Relevance
“…Visual learners use their eyes to process, acquire, comprehend information (Pashler et al, 2008). The result of the current study was in line with several previous studies who found that EFL students tend to prefer visual learning style (Manipuspika, 2020;Shuib & Azizan, 2015). By using different questionnaire of learning style, Prystiananta (2018) also found that visual learning was the most preferred learning style by EFL undergraduate students.…”
Section: Findings and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Visual learners use their eyes to process, acquire, comprehend information (Pashler et al, 2008). The result of the current study was in line with several previous studies who found that EFL students tend to prefer visual learning style (Manipuspika, 2020;Shuib & Azizan, 2015). By using different questionnaire of learning style, Prystiananta (2018) also found that visual learning was the most preferred learning style by EFL undergraduate students.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…Those The Art of Teaching English as a Foreign Language visual media are highly motivating for students to learn English and helping them to understand the content of teaching more easily (Philippe et al, 2020). When the students are motivated in learning, it is believed that they can show their best potential (Manipuspika, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the preliminary study done by the writer towards 34 millennial students of UKAW dealing with the learning strategies at EESP, the writer found that there were 29 students expecting improvements in learning strategies based on their preferences to help them learn effectively, especially in pandemic situation. This finding fits the statement stated by Manipuspika (2020) that understanding the styles of learning can be very useful for the students to learn in the way they learn best through the activities. It means that there should be any consideration and improvement towards the lecturers' teaching strategies to help them fit the students' needs in learning.…”
Section: Introductionsupporting
confidence: 89%
“…There is some research in ASEAN that has been carried out to determine the preferred learning method of EFL students. One of the research conducted by Manipuspika (2020), declares that visual learning styles are quite dominant in EFL students. She claims that this occurred because visual media such as LCD projectors assist students in the classroom.…”
Section: Introductionmentioning
confidence: 99%